Il “mondo alla rovescia”. Abbozzo di una teoria politico-fenomenologica della fuga - Tidona, Giovanni (Filosofia, 2023)
The discourse on escaping is primarily directed towards the who of escape. The question of how of escaping in its philosophical significance is normally neglected. For this purpose, it is necessary to rethink escape as a triple articulated phenomenological topology based on three vectors: escape as a start, as a transition and as a destination / refuge. By examining its political and spatial-philosophical characteristics (escape as a separation, as a non-place and as a fugue) as well its topological dimensions (earth as exile, see and desert, earth as asylum), escape emerges as a dynamic phenomenon that is due to reshape essential concepts and inverse traditional categories of politics.